PERBEDAAN KADAR HEMOGLOBIN MENGGUNAKAN METODE HB METER DAN HEMATOLOGY ANALYZER - Rahmatullah, Widia; Abdullah, Sulistiawati; Mardiyaningsih, Ana (Jurnal Ilmu Keperawatan, 2023)
Examination of hemoglobin levels before blood donation is an important check to certify that potential donors can donate blood. Hemoglobin levels can be measured using the hematology analyzer method where this method checks more quickly and the results issued usually have gone through quality control carried out by an in-house laboratory, it's just that this method has limitations including treatment, room temperature, must be controlled periodically. Checking hemoglobin levels can also be measured using the Hb meter method. Checking hemoglobin levels can also be done using Hb meters which are widely used by health services, such as clinical laboratories, health centers and hospitals. The advantages of the Hb meter include the results obtained faster and cheaper. This study aims to determine differences in the results of examination of hemoglobin levels using the Hb meter method with a hematology analyzer. The research method used is True Experiment with the type of research The Posttest Only Design. The sample in this study were 16 prospective blood donors at PMI Yogyakarta City. Respondents who had been given an explanation and signed an informed consent were then taken a sample of their venous blood and examined the hemoglobin level using the Hb meter and hematology analyzer methods. results are recorded and then data processing is carried out using univariate analysis and bivariate analysis. Based on the results of the study it was concluded that there was no significant difference between the results of examining hemoglobin levels using the Hb meter method and the Hematology Analyzer (p = 0.321 : p > 0.05). The average value of hemoglobin levels in the Hb meter method is 14.631 g/dl while the average value of hemoglobin levels in the Hematology Analyzer method is 14.294 g/dl.